Development and Quality Analysis of Web-Based Information Systems - Onno Widodo Purbo (Institute of Computer Science (IOCS), 2021)
With theThis study aims to develop a web-based seminar management information system and determine the quality level of the developed web-based seminar management information system, while the research method used in this study is Research and Development (R&D) with a waterfall development model that refers to software engineering principles. The stages that are passed are communication (communication), planning (planning), modeling (modeling), construction (construction), and distribution (deployment). Software quality analysis is carried out by adopting the ISO 25010 standard, namely aspects of functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability. The results of this study are 1) the seminar management information system was built using the PHP programming language and the Postgre database. The frameworks used are CodeIgniter and Admin LTE (Bootstrap). This information system has 7 user levels, namely administrator, committee (committee), reviewer, main speaker (presenter), second speaker (non-presenter), participant (audience), and visitor (guest). 2) the results of the analysis of software quality by adopting the ISO 25010 standard are as follows (1) function suitability aspects with 100% success; (2) the aspect of performance efficiency obtained a Yslow score of 92.97 (grade A); (3) the compatibility aspect can run well on the 4 tested web mails (4) the usability aspect obtained a raw SUS score of 73.00, acceptability ranges with acceptable results, grade scale with C results, and adjective ratings with good results (5) reliability aspects with 100% result; (6) security aspect with the result that the security vulnerability is at level 1 (low); (7) the maintainability aspect with the results of the maintainability index 90.81 (high category) (8) the portability aspect can run well on the 5 web browsers tested.